Hydrography of intertidal environments in Schleswig-Holstein, Germany: Bottsand - Joachim Schönfeld; Hermann W Bange; Helmke Hepach; Svenja Reents (PANGAEA, 2025)
The water level, salinity, air, and water temperatures were measured at Bottsand lagoon, Kiel Bight, Baltic Sea, and at Schobüll, German Bight, Wadden Sea. The measurements were collected at Bottsand from 2021-09-18 to 2024-10-12, and at Schobüll from 2021-09-24 to 2024-10-09. The temporal resolution is 20 minutes. Daily mean values were calculated and measurements during high waters were extracted form the data. An earlier data set of high-water temperature and salinity measurements taken at Schobüll from 2014-09-28 to 2019-11-20 is also included. The average temporal resolution of this data set is 12 hours and 16 minutes. High water times and high water levels from Husum tide gauge were included in case the water level sensors at Schobüll failed. Water level measurements from Holtenau tide gauge were included from 2023-10-18 to 2023-10-21 at a temporal resolution of 20 minutes in order to describe the 2023 Centennial Flood of the western Baltic. Data sets used for comparison of long-term trends were the daily mean air temperature and precipitation at Schobüll private weather station from 2021-09-26 to 2024-10-09, salinity and temperatures measurements taken in in surface waters at List Reede from 2014-01-20 to 2024-10-30, and weekly mean Elbe River discharges at Neu Darchau gauging station from 2014-01-08 to 2024-12-25. The purpose of data collection at Bottsand and Schobüll was to establish a 36-month time series of water level, temperature, and salinity for a baseline study to assess the hydrography in intertidal environments. Odyssey® data loggers (Dataflow Systems Ltd., Christchurch, New Zealand) were used to measure water level, temperature, and salinity. Xylem Ebro EBI-20T data recorders (Xylem Analytics Sales GmbH & Co. KG, Weilheim, Germany) were used to measure the air temperature at Bottsand and Schobüll.